Neue innovative Schrittmachersysteme – Kabellose und subkutane Implantate - Napp, Andreas; Reith, Sebastian (DMW - Deutsche Medizinische Wochenschrift, 2018)
Conventional transvenous pacemaker and ICD-therapy is associated with significant lead- and pocket-related problems. Leadless pacemaker and subcutaneous ICD (S-ICD) therapies are innovative technologies, that avoid these complications. To date two leadless pacemaker systems have been implanted percutaneously for isolated right ventricular pacing, the Nanostim™ and the Micra™ device. The S-ICD represents an alternative to the transvenous ICD for primary and secondary prevention of sudden cardiac death. New multicomponent leadless pacemakers, as well as the combination of leadless pacemaker and S-ICD, are promising therapeutic options in the future. This review describes the state of the art of leadless pacing and S-ICD-therapy.
Keywords: Kabelloser Schrittmacher; Herzschrittmacher; subkutaner ICD; S-ICD; Defibrillator